The IMPACT OF RATIONAL, EMOTIONAL, AND SPIRITUAL MOTIVES ON GEN Z'S SKINCARE PURCHASING DECISIONS IN JAMBI CITY - Tassya, Tassya Fitri Ramadhani; Yacob, Syahmardi; Musnaini, Musnaini (Journal of Business Studies and Management Review, 2025)
This study aims to analyze the influence of rational, emotional, and spiritual motives on skincare purchasing decisions among Generation Z in Jambi City. A quantitative approach was employed, with a total of 99 respondents selected through a purposive sampling technique. Data were collected using an online questionnaire distributed via Google Forms. The collected data were then processed using SPSS version 21, utilizing multiple linear regression analysis. The findings indicate that rational motives have a positive and significant impact on purchasing decisions. Additionally, emotional and spiritual motives also significantly influence skincare purchasing decisions. Furthermore, the simultaneous test results confirm that rational, emotional, and spiritual motives collectively have a significant effect on the skincare purchasing decisions of Generation Z in Jambi City.